2020
DOI: 10.1136/ijgc-2019-000994
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic and open radical hysterectomy in cervical cancer patients with tumor size ≤2 cm

Abstract: ObjectiveThere is recent evidence that demonstrates worse oncologic outcomes associated with minimally invasive radical hysterectomy when compared with open radical hysterectomy, particularly in patients with tumors >2 cm. The aim of our study was to retrospectively evaluate the oncological outcomes between laparoscopic and open radical hysterectomy in International Federation of Gynecology and Obstetrics(FIGO) 2009 stage IB1 (FIGO 2009) cervical cancer patients with tumor size ≤2 cm.MethodsA retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…The flaws are dependent on outdated methodology, confounding factors, heterogeneity of reporting of results, lack of replication, and a failure to interpret findings within the limitations of observational research methodology [29][30][31] Overall, the results reflect that in this large European population findings were consistent with recently published prospective data and confirmed by several retrospective population-based analyzes published since the LACC trial. [8][9][10][11][12][13][14][15] There are two prospective randomized trials exploring the role of minimally invasive surgery in patients with cervical cancer. The first is the RACC trial, 28 a Swedish multicentric prospective trial comparing robotic vs open surgery for the treatment of early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The flaws are dependent on outdated methodology, confounding factors, heterogeneity of reporting of results, lack of replication, and a failure to interpret findings within the limitations of observational research methodology [29][30][31] Overall, the results reflect that in this large European population findings were consistent with recently published prospective data and confirmed by several retrospective population-based analyzes published since the LACC trial. [8][9][10][11][12][13][14][15] There are two prospective randomized trials exploring the role of minimally invasive surgery in patients with cervical cancer. The first is the RACC trial, 28 a Swedish multicentric prospective trial comparing robotic vs open surgery for the treatment of early-stage cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, two recent manuscripts published in October of 2018 in NEJM (the LACC trial and a large epidemiologic study involving women from Cancer-Accredited hospitals in the United States) 8 9 demonstrated higher rates of recurrence and death in patients that underwent minimally invasive radical hysterectomy. Subsequently, a number of retrospective studies corroborated these findings, [10][11][12][13][14][15] resulting in a recent modification of the NCCN, European Society of Gynecological Oncology (ESGO), and ESMO guidelines. [16][17][18] The unexpected results of the LACC trial and other retrospective studies led to an ongoing discussion regarding the ideal surgical approach in patients with early cervical cancer.…”
Section: Original Researchmentioning
confidence: 99%
“…Recent studies evaluated the oncological outcomes in patients with cervical tumors ≤ 20 mm [24][25][26]; in particular, the study of Anchora et al [27] [27]. However, in a retrospective study of 815 women with tumor size ≤ 20 mm, in whom radical hysterectomy was performed by MIS in 255 cases and open surgery in 560 cases, the MIS approach was noted to be independently associated with a higher likelihood of recurrence (adjusted HR, 6.31; 95% CI 1.24-31.9) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Study design Matched 10 (5,11,13,15,16,19,28,30,41,43) 1.49 (1.19-1.88) 0.001 27.5 Fixed effect Retrospective 26 (6-10, 12, 14, 17, 18, 20-27, 29, 31-34, 42, 44-46) 1. (12,13,19,23,24,(27)(28)(29)(30)(31)(32)(33)(34)(42)(43)(44)(45)(46) 1. Small (at least one arm < 90) 18 (5-11, 14-18, 20-22, 25, 26, 41) 0.90 (0.67-1.20)…”
Section: Fixed Effectmentioning
confidence: 99%
“…Before LACC trial 22 (5-24, 41, 42) 0.89 (0.71-1.11) 0.289 0.0 Fixed effect After LACC trial 14 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(43)(44)(45)(46) 1. 17 (5, 11, 12, 17, 19, 21, 22, 24-26, 29, 31, 32, 41-43, 45) 1.06 (0.87-1.30) 0.555…”
Section: Published Yearmentioning
confidence: 99%